Analisis Tingkat Keramahan Lingkungan Alat Tangkap Pancing Ulur Tuna di Pelabuhan Perikanan Samudera Bitung Kota Bitung Sulawesi Utara - Fauziah Ivo; Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the potential resources utilized in Bitung City, Aertembaga District, is the industrial area and port area. With the large number of hand line tuna fishing gear used by fishermen at the Bitung Ocean Fishing Port, it is necessary to conduct research on the level of environmental friendliness of this fishing gear which aims to identify catches and determine the level of environmental friendliness of tuna hand line fishing gear. This research was carried out at the Bitung Ocean Fishing Harbor in November – December 2024. The research used was a Quantitative Descriptive method with a survey method, namely a method of collecting, presenting and analyzing data through interviews by providing a set of questions related to aspects of environmental friendliness according to 9 criteria. which refers to the FAO Code of Conduct for Responsible Fisheries (CCRF) 1995 to 25 respondents. The results obtained from calculating the environmental friendliness score are 31.4, which means that the fishing method using tuna hand lines at PPS Bitung is very environmentally friendly.